Distant-earthquake simulations considering source rupture propagation refining the seismic hazard of Hong Kong. - Megawati, Kusnowidjaja
Deterministic and probabilistic seismic hazard analyses should be complementary, in the sense that probabilistic analysis may be used to identify the controlling deterministic design-level earthquake events, and more sophisticated models of these events may then be developed to account for uncertainties that could not have been included directly in the probabilistic analysis. De-aggregation of the tentative uniform hazard spectra (UHS) in Hong Kong resulting from a probabilistic seismic hazard assessment (PSHA) indicates that strong and major distant earthquakes, rather than moderate local earthquakes, make the largest contribution to the seismic hazard level within the natural-period range longer than 0.3 s. Ground-motion simulations of controlling events located 90 and 340 km from Hong Kong, taking into account uncertainties in the rupture process, reveal that the tentative UHS resulting from the PSHA may have significantly underestimated the mid-to-long period components. This is attributed mainly to the adoption of double-corner source-spectrum models in the attenuation relationships employed in the PSHA. The results of the simulations indicate clearly that rupture directivity and rupture velocity can significantly affect the characteristics of ground motions, even from such distant earthquakes. The rupture-directivity effects have profound implications in elongating the second corner period where the constant velocity intersects the constant displacement, thus increasing the associated displacement demand. However, demands for acceleration and velocity are found to be not sensitive to the presence of the directivity pulses. Ground pulses resulting from forward rupture directivity of distant earthquakes have longer predominant periods than the usual near-fault directivity pulses. These long-period pulses may have profound implications for metropolises, such as Hong Kong and others in Southeast Asia, having large concentration of high-rise buildings.
Keywords: Rupture directivity; Rupture velocity; Distant earthquake; Ground-motion simulation; Hong Kong; Deterministic seismic hazard assessment